The Issue Of Human Life In Tran Buddhist Philosophy - Chinh, Asso. Prof., Dr. Doan; Chi, Dr. Trinh Thi Kim; Tung, Dr. Trinh Thanh (The journal of contemporary issues in business and government, 2021)
The article focuses on presenting human issues in Tran philosophy, through the viewpoints of human purpose, attitudes and actions; ethical values and intellectual and moral cultivation; about human life and death, imbued with the imprint of meditation, with typical thinkers such as Tran Thai Tong, Tue Trung Thuong si, and Tran Nhan Tong.